Clinico-bacteriological analysis for video-assisted thoracoscopic biopsy of non-tuberculous mycobacteria - Yamamichi, Takashi (J Thorac Dis, 2019)
BACKGROUND: The prevalence of non-tuberculous mycobacteria (NTM) has been increasing in recent years, and thus the number of related surgeries. In recent studies, a few recent studies reported that NTM patients require preoperative treatment. In addition, some cases are found to be granuloma suspected to be NTM (gsNTM) after surgery. We conducted a clinico-bacteriological examination of resected NTM and gsNTM cases we managed. METHODS: Between 2003 and 2017, 82 patients with NTM and gsNTM underwent video-assisted thoracoscopic (VATS) biopsy at our institution. The objectives of surgery, perioperative treatment, progression of NTM and gsNTM, and bacteriological data were analyzed. RESULTS: We enrolled 42 men and 40 women with a median age of 65 years. The bacteriological findings were Mycobacterium avium in 38 cases, M. intracellulare in 6 cases, M. kansasii in 3 cases, and gsNTM in 35 cases. The objectives of surgery were the diagnosis in 77 cases, and resistance to treatment in 6 cases. We performed postoperative treatment in 8 cases. There was no surgery-related (30-day mortality) death or complication. CONCLUSIONS: We analyzed surgical outcome for pulmonary NTM infections. We need to reconsider the surgical procedure for single pulmonary NTM lesion and whether adjuvant chemotherapy is necessary for NTM treatment.